Possibilities and Challenges in Occupational Injury Surveillance of Day Laborers - Lowry, Sarah J. (2010)
BACKGROUND: Day laborers in the US, comprised largely of undocumented immigrants from Mexico and Central America, suffer high rates of occupational injury according to recent estimates. Adequate surveillance methods for this highly transient, largely unregulated group do not currently exist. This study explores chart abstraction of hospital-based trauma registry records as a potential injury surveillance method for contingent workers and day laborers. We sought to determine the degree of completeness of work information in the medical records, and to identify day laborers and contingent workers to the extent possible. METHODS: Work-related injury cases from a hospital-based trauma registry (2001–2006) were divided by ethnicity (Hispanic vs. non-Hispanic origin) and presence of social security number (SSN: yes, no), resulting in four groups of cases. Medical records were abstracted for 40 cases from each group; each case was assigned values for the variables “day labor status” (yes, no, probably not, probable, unknown) and “employment type” (contingent, formal, unknown). RESULTS: Work information was missing for 60% of Hispanic cases lacking SSN, as compared with 33–47% of the other three groups. One “probable” day laborer was identified from the same group. Non-Hispanics with SSN were less frequently identified as contingent workers (5% as compared with 15–19%). CONCLUSIONS: This method revealed severe limitations, including incomplete and inconsistent information in the trauma registry and medical records. Approaches to improve existing resources for use in surveillance systems are identified. The potential of an active surveillance approach at day labor hiring centers is also briefly discussed.